2020
DOI: 10.1021/acs.jpcc.0c01708
|View full text |Cite
|
Sign up to set email alerts
|

Facile Decomposition of Organophosphonates by Dual Lewis Sites on a Fe3O4(111) Film

Abstract: Dimethyl methylphosphonate (DMMP) is used as a simulant for toxic nerve agents and pesticides, rendering the understanding of surface chemistry requisite to design effective materials for organophosphonate (catalytic) decomposition at room temperature. In this work, DMMP surface chemistry is studied on an iron oxide surface in a very well-defined environment using temperature-programmed reaction, isotopic labeling, scanning tunneling microscopy, X-ray photoelectron spectroscopy, and density functional theory. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 68 publications
1
16
0
Order By: Relevance
“…Adsorption of DMMP on CeO 2 (110) and (111) surfaces is a straightforward process. Similar to other metal oxides, ,,, DMMP is adsorbed on the Ce atom via its phosphoryl oxygen, as depicted in Figure a,b. The calculated energy of DMMP adsorption on the CeO 2 (110) surface (−164.8 kJ mol –1 ) is considerably higher than that on the (111) surface (−116.9 kJ mol –1 ), which is, most likely, explained by a stronger electrostatic repulsion between the phosphoryl oxygen of DMMP and a surface oxygen atom on the CeO 2 (111) surface.…”
Section: Resultsmentioning
confidence: 85%
“…Adsorption of DMMP on CeO 2 (110) and (111) surfaces is a straightforward process. Similar to other metal oxides, ,,, DMMP is adsorbed on the Ce atom via its phosphoryl oxygen, as depicted in Figure a,b. The calculated energy of DMMP adsorption on the CeO 2 (110) surface (−164.8 kJ mol –1 ) is considerably higher than that on the (111) surface (−116.9 kJ mol –1 ), which is, most likely, explained by a stronger electrostatic repulsion between the phosphoryl oxygen of DMMP and a surface oxygen atom on the CeO 2 (111) surface.…”
Section: Resultsmentioning
confidence: 85%
“…In the case of our experiment, it is possible that dimethyl ether formation occurs via the interaction of either methanol resulting from DMMP decomposition or a surface methoxy with a P–OCH 3 species on a cluster-bound phosphonate. In a recent rigorous study involving the decomposition of DMMP on a well-defined Fe 3 O 4 (111) surface in UHV, it was convincingly demonstrated via isotopic labeling and accompanying DFT calculations that dimethyl ether formation at around 600 K during TPD/R experiments was solely due to intramolecular reaction of surface-bound MMP species, complicating this picture even further . That work also demonstrated that oxygen adatoms on the surface, that is, undercoordinated oxygen atoms, are key to the observed DMMP decomposition pathways.…”
Section: Resultsmentioning
confidence: 96%
“…1 Recent studies have shown that metal oxides can effectively destroy CWAs due to their high surface area, a large number of highly reactive edges, corner defect sites, unusual lattice planes, and high surface-to-volume ratios. In particular, metal oxides, such as CaO, 3,4 MgO, 5,6 ZnO, [7][8][9] TiO 2 , 10-16 Al 2 O 3 , [17][18][19][20] Fe 3 O 4 , 21 and CuO 22 are candidates as adsorbents for enhancing the decomposition of CWAs. In γ-Al 2 O 3 , Al atoms in the bulk exhibit either a tetrahedral or octahedral coordination.…”
Section: Introductionmentioning
confidence: 99%